2022
DOI: 10.1002/poh2.18
|View full text |Cite
|
Sign up to set email alerts
|

Nonselective beta‐blockers reduce mortality in patients with acute‐on‐chronic liver failure

Abstract: Aim Nonselective beta‐blockers (NSBBs) can reduce the incidence of complications in patients with cirrhosis and prolong survival. The safety and efficacy of NSBBs in real‐world settings in patients with acute‐on‐chronic liver failure (ACLF) identified by the Asian Pacific Association for the Study of Liver criteria are unknown. This study aimed to assess the safety and efficacy of NSBBs in patients with Asian Pacific Association for the Study of Liver (APASL)‐defined ACLF Methods In this retrospective, multice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 28 publications
(83 reference statements)
0
0
0
Order By: Relevance
“…The use of NSBBs in PH is well-studied and has a pleiotropic mechanism. In addition to being economical to use, recent studies have demonstrated their pleiotropic effects, like preventing bacterial translocation, antioxidant properties, containing further nonbleed decompensations, and portal hypertensive gastropathy progression, as well as improving survival in ACLF (32)(33)(34)(35). Adding another rate-controlling agent, ivabradine, to NSBB has shown some promising results, achieving better hemodynamics, reducing the incidence of acute kidney injury (AKI) and HE, and…”
Section: Primary Prophylaxis Of Vhmentioning
confidence: 99%
“…The use of NSBBs in PH is well-studied and has a pleiotropic mechanism. In addition to being economical to use, recent studies have demonstrated their pleiotropic effects, like preventing bacterial translocation, antioxidant properties, containing further nonbleed decompensations, and portal hypertensive gastropathy progression, as well as improving survival in ACLF (32)(33)(34)(35). Adding another rate-controlling agent, ivabradine, to NSBB has shown some promising results, achieving better hemodynamics, reducing the incidence of acute kidney injury (AKI) and HE, and…”
Section: Primary Prophylaxis Of Vhmentioning
confidence: 99%